Professional psychological qualities of Chinese medical students: theoretical models, questionnaire development, and relationship with mental health - Luo, Wenping; Fan, Wenshu; Xia, Yanglin; Dou, Yanchun; Du, Juan (Frontiers in Psychology, 2024)
Introduction Professional psychological qualities are crucial for individuals’ career development and overall well-being, especially in clinical medical professions. Medical students often face significant work, academic, and doctor-patient communication pressures, which can challenge their mental and emotional health. Measuring and understanding the relationship between medical students’ professional psychological qualities and their mental health is of significant practical importance. Methods This study developed a comprehensive professional psychological qualities scale through a series of qualitative and quantitative studies, consisting of three main components and thirteen secondary dimensions. The scale’s reliability was assessed using Cronbach’s α coefficients. In Study 2, the scale was administered to 972 medical students to explore their anxiety and depression levels. A simple mediation analysis was conducted to investigate the relationship between professional psychological qualities, anxiety, and depression. Results The professional psychological qualities scale demonstrated satisfactory reliability, with a total scale α coefficient of 0.947 and subscale α coefficients ranging from 0.895 to 0.933. The mediation analysis revealed that medical students’ professional psychological qualities directly negatively impact depression levels and indirectly positively influence them via their effects on anxiety levels, exhibiting an overall masking effect unrelated to depression levels. Discussion This study addresses the gap in research on the professional psychological qualities of medical students by providing a reliable measurement tool. The findings shed light on the complex mechanisms through which these qualities impact the mental health process. The scale can be used by other researchers to assess medical students’ professional psychological qualities and further investigate their relationship with mental health outcomes.